Kant's cosmopolitics contemporary issues and global debates - Brown, Garrett Wallace; Telegdi-Csetri, Áron (Edinburgh University Press, 2019)
This volume explores Kant's cosmopolitanism and its implications for a Kantian-inspired cosmopolitics. The contributors provide a definitive source and specification of key new areas in the field of Kantian cosmopolitanism and how it is integral to current debates in political theory, political philosophy and international relations.